Research Analysis of Cyber Security (Global Journal of Computer Science and Technology, 2015)
In an age of cyber technology with it fast pacing and ever evolving, securing data in cyber space is a major enigmawhich needs to be resolved.With vulnerabilities everywhere, data security and privacy is always at risk. This specially comes in play when services of third party are used knowingly or unknowingly. Government and business organizations are testing and implementing security and monitoring techniques to stand a better chance in raging war against cyber-crimes. Moreover, the formulation of new methods also poses new limitations of the systems as well as the users like lack of efficiency or complexity which need to be resolved in order to get better results. In this research paper some of those limitations and their solutions are discussed.
Keywords: cybercrime; security; complexity; usage; efficiency